2022
DOI: 10.3390/v14071355
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Tests for Rapid Detection of Porcine Epidemic Diarrhea Virus: A Systematic Review and Meta-Analysis

Abstract: The timely and accurate diagnosis of porcine epidemic diarrhea virus (PEDV) infection is crucial to reduce the risk of viral transmission. Therefore, the objective of this review was to evaluate the overall diagnostic accuracy of rapid point-of-care tests (POCTs) for PEDV. Studies published before 7 January 2022 were identified by searching PubMed, EMBASE, Springer Link, and Web of Science databases, using subject headings or keywords related to point of care and rapid test diagnostic for PEDV and PED. Two inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Recovery rates up to 75% from mouse feces with 0.75 mL min −1 throughput enteric diseases are also a common problem in modern swine farming and POC devices developed for veterinary use could be suitable for adaptation to human samples and diagnostic approaches. 329 In the following, considering the lack of literature on microfluidic devices specifically applied to POC clinical diagnosis of human GTI, we will extend our discussion to a selection of recent approaches covering pathogen detection from foodborne or nonhuman samples. Table 4 provides an overview of recent approaches for GTI pathogen detection.…”
Section: Giardia Cysts Purification Using Spiral Inertial Microfluidicsmentioning
confidence: 99%
“…Recovery rates up to 75% from mouse feces with 0.75 mL min −1 throughput enteric diseases are also a common problem in modern swine farming and POC devices developed for veterinary use could be suitable for adaptation to human samples and diagnostic approaches. 329 In the following, considering the lack of literature on microfluidic devices specifically applied to POC clinical diagnosis of human GTI, we will extend our discussion to a selection of recent approaches covering pathogen detection from foodborne or nonhuman samples. Table 4 provides an overview of recent approaches for GTI pathogen detection.…”
Section: Giardia Cysts Purification Using Spiral Inertial Microfluidicsmentioning
confidence: 99%
“…The 3D chemical structures of chrysin in an SDF format (PubChem CID, 5281607) were retrieved from the chemical database PubChem available on the NCBI website 2 (33). The OpenBabel online software 3 was used to convert the SDF files of the ligands to PDB format. The ligands were prepared by detecting the torsion root, correcting the torsion angles, assigning charges, optimizing using UFF (Universal force field), and finally converting them to pdbqt format to generate 3D atomic coordinates of the molecules (34).…”
Section: Ligand Preparationsmentioning
confidence: 99%
“…Porcine epidemic diarrhea (PED), one of the acute enteritis infections, is characterized by vomiting and watery diarrhea ( 1 ) and caused by the porcine epidemic diarrhea virus (PEDV) (genus alpha coronavirus, the order Nidovirales ) and has always been a limiting factor for the healthy development of the pig breeding industry ( 2 ). It usually threatened neonates’ survival rates, leading to the growth retardation of weaned piglets ( 3 ), which caused enormous economic losses for the global swine industry and international trade ( 4 ). PEDV is very destructive to the intestinal barrier of piglets and has a high mortality rate of 95% for those under 2 weeks of age piglets ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the conserved regions on the spike gene have been targets for the design of specific universal primers and probes in the development of molecular detection of PEDV isolates. In 2022, Li and coworkers published a systematic review and meta-analysis of the diagnostic accuracy of lateral flow immunochromatography assay (ICA)-based procedures and nucleic acid isothermal amplification (NAIA)-based point-of-care tests (POCTs) for detecting PEDV [ 7 ]. Their study revealed that NAIA-based POCTs had a better diagnostic performance than ICA-based POCTs, and both tests showed acceptable diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%